Isolamento e identificação de Salmonella sp. e Campylobacter spp. em amostras de carne e swab cloacal, de tartaruga da amazônia (Podocnemis expansa) - Carneiro, Bruno Ferreira (2016)
The Arrau river turtle is the best known species of the genus Podocnemis and most testudines of freshwater in South America. In the North and Central West regions of the country is common to commercial production of the species P. expansa, but there are still parameters for to improve the production process and ensure the microbiological quality of meat produced. This study aimed to determine the presence of Salmonella sp. and Campylobacter spp. in skeletal striated muscle samples from the fillet region and forelimb and hindlimb, as well as the realization of cloacal swab. Skeletal muscle tissue of 20 males were picked with sterilized surgical instruments, packed in sterile vials and analyzed in the Laboratory of Microbiology and Food Technology Research Centre in Food UFG/EVZ and Bacteriological tests Laboratory and Anatomopathological of Birds of UFG/EVZ for evaluation according to the industry protocol. In the survey by Salmonella sp., Two samples (2/240) 0.83%, were positive for the bacterium gender researched and compared the search for microorganisms of the genus Campylobacter spp., were not detected microorganisms in the samples. To evaluate the results related to microbiology, we performed the Fisher Exact Test (p <0.05). The statistical test showed no statistical difference in relation to the treatment (p = 0.4737) and (p = 0.4979), relating the area of harvest, also not statistically significant. The data were important for improving the quality of carcasses slaughtered the species.